2014
DOI: 10.1513/annalsats.201404-152oc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pleural Effusion Drainage on Oxygenation, Respiratory Mechanics, and Hemodynamics in Mechanically Ventilated Patients

Abstract: Drainage of large (≥500 ml) pleural effusion in mechanically ventilated patients improves oxygenation and end-expiratory lung volume. Oxygenation improvement correlated with an increase in lung volume and a decrease in transpulmonary pressure, but was less so in patients with ARDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 32 publications
2
51
3
3
Order By: Relevance
“…This reduction in ventilator performed work might predict a reduction in the work performed by the spontaneously breathing patient. Razazi et al reported improvement in respiratory system compliance, end-inspiratory transpulmonary pressure, PaO 2 / FIO 2 ratio and end-expiratory lung volume [43]. A lesser improvement in oxygenation occurred in patients with ARDS.…”
Section: Assessment Of Pleural Effusionmentioning
confidence: 98%
“…This reduction in ventilator performed work might predict a reduction in the work performed by the spontaneously breathing patient. Razazi et al reported improvement in respiratory system compliance, end-inspiratory transpulmonary pressure, PaO 2 / FIO 2 ratio and end-expiratory lung volume [43]. A lesser improvement in oxygenation occurred in patients with ARDS.…”
Section: Assessment Of Pleural Effusionmentioning
confidence: 98%
“…In mechanically ventilated patients, improvements in PaO 2 :FiO 2 have been associated with the volume drained [14] and the increase in end-expiratory lung volume [15 ▪ ]; those with lower PaO 2 :FiO 2 ratios appeared to have greater benefit. Patients with acute respiratory distress syndrome appeared to have less improvement in gas exchange [15 ▪ ,16]. In mechanically ventilated patients with CHF effusions, the improvement in PaO 2 :FiO 2 after thoracentesis correlated inversely with pleural elastance [17].…”
Section: Pathophysiological Effects Of a Pleural Effusionmentioning
confidence: 99%
“…A further study [8] in a medical ICU demonstrated an early improvement in P/F ratio at 3 h post pleural drainage, and sustained at 24 h post intervention. A recent meta-analysis of a total 118 patients demonstrated an overall 18% improvement in the PaO 2 /FiO 2 ratio after effusion drainage [13].…”
Section: Discussionmentioning
confidence: 87%
“…Results from previous research Razazi et al [8], showed that PaO 2 / FiO 2 before drainage and 24 h after drainage was 191 ± 69 versus 250 ± 106 respectively. Based on this the needed sample is 40 cases.…”
Section: Sample Sizementioning
confidence: 90%